Debt-to-Income Ratio and Financial Vulnerability of Rural Households: Evidence from Weekly Microfinance Practices in Boawae District, Nagekeo Regency - Maria Yasinta Deme; Ernesta Wae (CV. Namora dan Riona Bersaudara, 2026)
The proliferation of weekly microfinance known as